Terapi Latihan pada Fase Satu Pasca Operasi Rekonstruksi Ruptur Anterior Cruciate Ligamentum Sinistra - Wurgani, Aunike Arum Meta; Wibisono, Irawan (UI Scholars Hub, 2024)
Anterior Cruciate Ligament (ACL) reconstruction is a surgical procedure involving the grafting of the ACL using tendon tissue. This procedure aims to restore knee stability and joint fixation following an ACL injury. Post-ACL reconstruction often leads to complications such as pain, edema, reduced range of motion, and muscle weakness. The physiotherapy program in this case aims to evaluate the effects of physiotherapy interventions, including quadriceps setting, hamstring setting, straight leg raise (SLR), heel slide, ankle pumping, bridging, and prone hang exercises, in reducing edema and pain, as well as improving the range of motion and muscle strength in the knee joint after ACL reconstruction. This study was conducted on one respondent in phase 1 post-ACL reconstruction, with therapy administered over four sessions. After three therapy sessions, results showed a reduction in pain and edema, along with an increased range of motion and muscle strength. The conclusion of this study is that a comprehensive physiotherapy program in phase 1 post-ACL reconstruction is effective in reducing pain and edema, as well as improving the range of motion and muscle strength.